Un santo fra gli Stati. La canonizzazione di Filippo Neri nell’Europa della Controriforma - Gotor, Miguel (Studi Politici, 2025)
In 1622 Pope Gregory xv canonized Isidore the Farmer, Teresa of Avila, Ignatius of Loyola, Francis Xavier and Philip Neri. This paper focuses on the history of the canonization process in honor of the founder of the Oratory and, also, on the support that his cause received from the Grand Duchy of Tuscany and France. On the other hand, it highlights how a number of decisions (multiple canonization, order of precedence of the saints, papal bull, ceremonial decoration) hinge on a political and diplomatic negotiation carried out by the Pope with the aim of reaching a balance between France and Spain, showing the need to emphasize the «roman» character of those canonizations.